Precision laser beam measurements - Basil A. Omar (1990)
The work described in this thesis is concerned with two main areas of investigation. The first involves the measurement and characterisation of the fluorescence of various doped glasses when excited by a pulsed ultra-violet laser beam, with a view to finding a material which acts as a suitable ultra-violet to visible image converter. A system is described, based on a glass fluorescer, which writes the beam profile of a single-shot KrF laser directly into computer memory and hence permits powerful image processing, and measurements to be made on the laser beam profile. The system was developed primarily for the spatial profiling of 'Sprite', Europe's largest ultra-violet laser, and is currently in routine use at the Rutherford Appleton Laboratory for this purpose [continued]…